CAN WOMEN BE EMPOWERD THROUGH ENTREPRENEURSHIP? A LESSION FROM THE EXPERIENCE - Kavitha, V.O. (International Journal of Psychosocial Rehabilitation, 2017)
Women in Ethiopia account for the large share (60%) of the informal economy operators and running Micro and Small Enterprises (MSEs). Beyond participating in productive activities such as agriculture, trade and industry, women have multiple roles in the society. As a result of empowering women, there will be a development in the human capital whereby a continuity of the enterprises can be ensured. Though more number of women is engaged in MSEs at Hawassa town, how far these MSEs have contributed to achieve the empowerment of women is unknown due to dearth of studies. Hence, this paper examines the role of MSEs in women empowerment. To address the objectives, primary data was collected through pre tested interview schedule from 121 enterprises owners who were identified by stratified random sampling technique. Different indicators such as economic improvement, social improvement, skill development, political improvement were used to assess the impact of entrepreneurship on women empowerment. The collected data was complied and analyzed by using appropriate statistical tools and the results obtained are presented in the form of tables and graphs for easy understanding. In addition, multiple liner regression analysis was carried out to identify the influential factors which affect the participation of women in MSEs. The results of the research show that MSEs provide employment opportunities to the poor, house wives, students and unemployed who have no other means of income and opportunity in the formal sectors. Women entrepreneurs gained ability to make decision on family expenditure and money utilization after their involvement in MSEs. Also they benefited in terms of securing family livelihood, freedom from domestic domination, sanction for social involvement, acquiring skill and knowledge of business which support them for empowerment. Although women entrepreneurship is significant in terms of reducing the household vulnerability in terms of nutrition, cloths, education and other expenses, they are also facing some problems. Many of them are not reaching their growth potential due to various factors mainly lack of market linkage, business premises, high material cost, lack of finance and others. Based on the findings policy options are forwarded.